2015
DOI: 10.1590/s0080-623420150000700015
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensos com e sem doença renal: avaliação de fatores de risco

Abstract: RESUMO Objetivo Comparar pacientes hipertensos com e sem doença renal e identificar fatores associados à condição clínica e tratamento anti-hipertensivo. Método Estudo transversal realizado com pacientes admitidos em clínica médica de um hospital universitário da cidade de São Paulo. Os dados foram coletados por meio de análise do prontuário. Valores de p<0,05 foram considerados significantes. Resultados Dos 386 pacientes avaliados, 59,3% eram hipertensos e destes 37,5% tinham doença renal crônica. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…A similar investigation conducted among hypertensive patients in Donkorkrom in the Eastern Region yielded a prevalence of 50%, 43%, and 46% using CG, MDRD, and CKD-EPI equations, respectively [ 15 ]. In other jurisdictions, a high burden of renal dysfunction among hypertensive individuals was reported in Nigeria [ 16 , 17 ], Cameroon [ 18 , 19 ], Guinea [ 20 ], Brazil [ 21 ], and Qatar [ 22 ]. However, renal dysfunction prevalence rates lower than the findings of this study have been reported among some Ghanaian (4.1% and 0.5%) [ 23 ] and South African (7.8%) [ 24 ] populations.…”
Section: Discussionmentioning
confidence: 99%
“…A similar investigation conducted among hypertensive patients in Donkorkrom in the Eastern Region yielded a prevalence of 50%, 43%, and 46% using CG, MDRD, and CKD-EPI equations, respectively [ 15 ]. In other jurisdictions, a high burden of renal dysfunction among hypertensive individuals was reported in Nigeria [ 16 , 17 ], Cameroon [ 18 , 19 ], Guinea [ 20 ], Brazil [ 21 ], and Qatar [ 22 ]. However, renal dysfunction prevalence rates lower than the findings of this study have been reported among some Ghanaian (4.1% and 0.5%) [ 23 ] and South African (7.8%) [ 24 ] populations.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is considered as both cause and consequence of CKD and mainly compromises the kidneys' vascular structures. 20 The malignant and accelerated form of CKD can cause severe microvascular kidney disease, characterized by malignant nephrosclerosis, in which the renal arteriole wall's muscular layers thicken, which reduces the flow and causes renal ischemia. However, microvascular kidney disease may progress more slowly in patients with chronic hypertension, characterizing a hyaline arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…More than half (59.3%) of the 386 patients evaluated in a general medical clinic of a university hospital in the city of São Paulo presented arterial hypertension. This is because, besides to being one of the most important causes for the establishment and development of the disease, arterial hypertension is a consequence of chronic kidney disease (6,(13)(14) .…”
Section: Discussionmentioning
confidence: 99%